Dysregulations of sonic hedgehog signaling in MED12‐related X‐linked intellectual disability disorders - Srivastava, Siddharth (Mol Genet Genomic Med, 2019)
BACKGROUND: Mutations in mediator of RNA polymerase II transcription subunit 12 homolog (MED12, OMIM 300188) cause X‐linked intellectual disability (XLID) disorders including FG, Lujan, and Ohdo syndromes. The Gli3‐dependent Sonic Hedgehog (SHH) signaling pathway has been implicated in the original FG syndrome and Lujan syndrome. How are SHH‐signaling defects related to the complex clinical phenotype of MED12‐associated XLID syndromes are not fully understood. METHODS: Quantitative RT‐PCR was used to study expression levels of three SHH‐signaling genes in lymophoblast cell lines carrying four MED12 mutations from four unrelated XLID families. Genotype and phenotype correlation studies were performed on these mutations. RESULTS: Three newly identified and one novel MED12 mutations in six affected males from four unrelated XLID families were studied. Three mutations (c.2692A>G; p.N898D, c.3640C>T; p.R1214C, and c.3884G>A; p.R1295H) are located in the LS domain and one (c.617G>A; p.R206Q) is in the L domain of MED12. These mutations involve highly conserved amino acid residues and segregate with ID and related congenital malformations in respective probands families. Patients with the LS‐domain mutations share many features of FG syndrome and some features of Lujan syndrome. The patient with the L‐domain mutation presented with ID and predominant neuropsychiatric features but little dysmorphic features of either FG or Lujan syndrome. Transcript levels of three Gli3‐dependent SHH‐signaling genes, CREB5, BMP4, and NEUROG2, were determined by quantitative RT‐PCR and found to be significantly elevated in lymphoblasts from patients with three mutations in the MED12‐LS domain. CONCLUSIONS: These results support a critical role of MED12 in regulating Gli3‐dependent SHH signaling and in developing ID and related congenital malformations in XLID syndromes. Differences in the expression profile of SHH‐signaling genes potentially contribute to variability in clinical phenotypes in patients with MED12‐related XLID disorders.